El declive de los séquitos de los virreyes mexicanos del siglo XVIII: Tendencias y excepciones - Rosenmüller, Christoph (2024)
In this article, I argue that the entourages of the viceroys traveling to New Spain declined notably during the eighteenth century, but with marked exceptions. While the aristocrats of the early century brought sizable retinues, a modest group of twenty criados (retainers) accompanied the Marquis of Casafuerte (1722-1734). Then Juan Francisco de Güemes y Horcasitas reinforced this transformation in 1746, when arriving from another posting in Spanish America with his wife, eight children, and perhaps a handful of criados. Some viceroys married to wives of significant social importance broke with the trend towards modesty, however these vicereines were entitled to their own criadas (female retainers) and criados to serve them, contributing to larger entourages. For that reason, the Marquis and Marquise of las Amarillas traveled with their son and sixty-six criados and criadas during the mid-century, while thirty-three criados and criadas came with the Marquis of Branciforte and María Antonia de Godoy y Álvarez de Faria in the year 1794. An important countercurrent jostled with the steady decline of viceregal patronage during the century.